Aspects of policy in the history of the College of Agriculture, University of the Philippines Los Baños. - Velasco, Jose R. (Philippines Rushing Water Publishers, 1995)
"This is an attempt to review the policies (both expressed and implied) in the University of the Philippines College of Agriculture and later the University of the Philippines Los Baños (UPLB). Even at the beginning, teaching and research has been its twin objective. This was justified by the thought that, as an institution at college level, it should be at the forefront of knowledge in tropical agriculture, but, since such knowledge in the tropics was meager and still evolving local research must complement teaching. The efforts at moulding the young minds of the students were designed to inculcate in them the urge to alleviate the rural environment and to love progressive farm life. One admirable desire of the initial expatriate faculty was to build up local expertise. Towards this end, students with high scholarship rating were employed as assistants and were imbued with the disciplines in a particular field. they were later sent abroad for advanced training and, on their return, were made to assume the responsibilities of teaching and research. Thus there was engendered an atmosphere of discipline and scholarship on the campus which was epitomized in the term "Los Baños spirit". The tranquility and trend towards excellence were abruptly disturbed by the chaos brought about by the World War II in the Pacific. After the war, the process of rebuilding was kindly assisted by the American government in the form of the Cornell-Los Baños contract. New directions were taken and greater responsibilities were assumed, ably charted by well-meaning American friends. Complacently, the local leadership at UPLB rode on the crest of the movement towards modernization and service to the country -- and incidentally, the international community."
Keywords: College of Agriculture -- University of the Philippines Los Baños; University of the Philippines Los Baños (UPLB); History -- Philippines